Methodology of calculation of time reserves when planning the duration of NPP construction - A. S. Pavlov; R. V. Ostrovskii (Vestnik MGSU)
Introduction. The issues of risk and problem situations arising during the construction of nuclear power plants, as well as methods of response and prevention of such scenarios are considered. The available analogues of the developed system among the known information systems which carry out calculations of calendar-network models and construction completion forecasts are analyzed.Materials and methods. In particular, the methodology of creating a system of time reservation during the formation and approval of calendar-network schedules of construction and installation works is highlighted. A step-by-step plan of initial data preparation, necessary statistical analysis and direct calculation of time reserves by Monte-Carlo method using the software package of the same name developed within the framework of the current research is presented. As the initial data, the information of the analysis of disruption of the deadlines of already completed works at reference NPP with a certain classification, as well as the results of an expert survey on the influence of internal and external factors on the duration of plant construction are used.Results. Examples of using the development within the process of managing the construction schedule of El-Dabaa NPP in the Arab Republic of Egypt are described. The possibility of applying this methodology at different levels of project management is indicated.Conclusions. A generalized conclusion on the issue of determining the duration of construction of nuclear power plants taking into account the formation of time reserves for work schedules, a step-by-step plan for calculating time reserves and positive approbation of the methodology for NPP construction is formulated.